Polyimide as well as preparation method and application thereof

By using polyimide materials with a high temperature decomposition temperature exceeding 500℃, the problem of poor thermal stability of lithium-ion battery separators at high temperatures is solved, and higher heat resistance and wetting are achieved, and the safety and performance of the battery are enhanced.

CN119529276APending Publication Date: 2025-02-28GREEN IND INNOVATION RES INST OF ANHUI UNIV

Patent Information

Application Number
CN202411592879.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Traditional lithium-ion battery separators have poor thermal stability under high temperature conditions, and the failure of adhesive bonding causes powder loss of the ceramic coating, affecting battery safety and wetting.

Method used

Polyimide material is used, with a decomposition temperature above 500°C and has good thermal properties and adhesion. It is used to prepare lithium-ion battery separators, provide a stable framework structure and enhance adhesion.

Benefits of technology

It improves the heat resistance and wetting properties of the lithium-ion battery separator, avoids the powdering and separation of the ceramic coating at high temperatures, and enhances the safety and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529276A_ABST
    Figure CN119529276A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of organic polymer materials and the technical field of lithium batteries, in particular to polyimide and a preparation method and application thereof.The preparation method of the polyimide comprises the steps that in the inert gas atmosphere, a first solvent, a first monomer and a second monomer are subjected to a mixed reaction, pyridine and acetic anhydride are added, a reflux reaction is conducted, cooling is conducted, and the polyimide is obtained. And adding a second solvent, stirring, carrying out suction filtration, and drying. The polyimide is resistant to high temperature, the decomposition temperature is 500 DEG C or above, and the polyimide has good thermal performance, meanwhile, when the polyimide is applied to preparation of the lithium ion battery diaphragm in the form of nanofibers and nanoparticles, due to the fact that the polyimide has cohesiveness, the problem that the cohesiveness of a binder fails is solved, and due to the fact that the polyimide contains ether bonds and has higher affinity with electrolyte, the service life of the polyimide is prolonged. The wettability of the battery is improved; meanwhile, the polyimide is simple in preparation method, suitable for mass production and convenient for commercialized popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of organic polymer materials and lithium battery technology, and in particular to a polyimide and a preparation method and application thereof. Background Art

[0002] Most commercial lithium-ion battery separators use polyethylene or polypropylene separators or ceramic-coated separators. Polyethylene or polypropylene has poor thermal shrinkage performance, which leads to safety hazards of lithium-ion batteries. Ceramic-coated separators fail to fundamentally solve the thermal performance defects of polyolefin separators. Under high temperature conditions, the bonding of the bonding material between the ceramic and the separator decreases, causing the ceramic to fall off and powder, reducing the safety performance of the separator. High-energy-density batteries have gradually increased their requirements for wettability. Therefore, it is of great practical significance to urgently develop a high-temperature resistant separator material. Summary of the invention

[0003] The purpose of the present invention is to solve the problem that the traditional lithium-ion battery has poor thermal stability and the ceramic coating loses powder due to the failure of the adhesiveness of the binder under high temperature conditions, thereby providing a polyimide and a preparation method and application thereof. The polyimide is resistant to high temperatures, has a decomposition temperature of more than 500°C, has good thermal properties, and the polyimide fiber provides a stable skeleton structure for the diaphragm, further increasing the heat resistance of the diaphragm. At the same time, when the polyimide is used in the form of nanofibers and nanoparticles to prepare lithium-ion battery diaphragms, the problem of the failure of the adhesiveness of the binder is avoided because of its own adhesiveness, and the affinity of the ether bond with the electrolyte is stronger because of the ether bond itself, thereby improving the wettability of the battery. At the same time, the preparation method of the polyimide is simple. In the process of using the polyimide in the form of nanofibers and nanoparticles to prepare diaphragms, water is used as a solvent. Compared with the traditional oily organic solvent coating system, the polyimide is green, environmentally friendly, pollution-free, and has lower cost, is suitable for mass production, and is convenient for commercial promotion.

[0004] In order to achieve the above object, in a first aspect, the present invention provides a method for preparing a polyimide, the preparation method comprising:

[0005] In an inert gas atmosphere, the first solvent, the first monomer and the second monomer are mixed and reacted, pyridine and acetic anhydride are added, refluxed and cooled to obtain a polyimide slurry, the second solvent is added, stirred, filtered and dried.

[0006] Preferably, the first solvent is selected from one or two or more of N-methylpyrrolidone, dimethylacetamide and N,N-dimethylformamide.

[0007] Preferably, the first monomer is selected from one or two or more of aromatic dibasic acid anhydrides, aromatic heterocyclic dibasic acid anhydrides and aliphatic dibasic acid anhydrides.

[0008] More preferably, the second monomer is a diamine containing an alkyl ether group or a blended diamine obtained by mixing a diamine containing an alkyl ether group with other diamines; wherein,

[0009] The general structural formula of the diamine containing an alkyl ether group is shown in Formula II:

[0010]

[0011] More preferably, the inert gas is nitrogen and / or argon.

[0012] More preferably, the second solvent is an alcohol, preferably ethanol and / or methanol.

[0013] Preferably, the first monomer is selected from one or two or more of biphenyltetracarboxylic dianhydride, cyclobutanetetracarboxylic dianhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, pyromellitic dianhydride, 1,2,3,4-butanetetracarboxylic dianhydride, benzophenonetetracarboxylic dianhydride, 4-phthalic anhydride)formyloxy-4-phthalate, diphenyl ether tetracarboxylic dianhydride, p-phenylene-diphenyltrimethylol dianhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, hexafluoro dianhydride and bisphenol A diether dianhydride.

[0014] Preferably, the structural formula of the diamine containing an alkyl ether group in the second monomer is selected from one of Formula A to Formula C;

[0015]

[0016] More preferably, the other diamines in the second monomer are selected from one or two or more of 4,4-diaminodiphenyl sulfone, 3,4-diaminodiphenyl sulfone, 3,3-diaminodiphenyl sulfone, m-phenylenediamine, p-phenylenediamine, pyridinediamine, naphthalenediamine, butanediamine and pentamethylenediamine 3,6-thioanthracene diamine.

[0017] Preferably, the mass ratio of the first solvent to the first monomer is 3-15:1.

[0018] Preferably, the molar ratio of the first monomer to the second monomer is 1:0.9-1.2.

[0019] Preferably, the conditions of the mixed reaction include: temperature of 0-15° C. and time of 1-3 h.

[0020] More preferably, the reflux reaction time is 4-6 h.

[0021] In a second aspect, the present invention provides a polyimide prepared according to the preparation method described in the first aspect, wherein the repeating unit of the polyimide comprises: a structure shown in Formula I:

[0022]

[0023] In formula I, X is a group linking two carbonyl groups on the imide ring, which is provided by the first monomer;

[0024] n, a are integers, a, n ≥ 1.

[0025] In a third aspect, the present invention provides a use of the polyimide described in the second aspect in preparing a lithium battery.

[0026] In a fourth aspect, the present invention provides a method for preparing a lithium battery separator, the method comprising: mixing polyimide, ceramic and an additive in the presence of a dispersion to obtain a coating slurry, coating the coating slurry on a surface of a polyolefin base film, and drying; wherein:

[0027] The polyimide is the polyimide described in the second aspect.

[0028] Preferably, the polyimide is provided in the form of polyimide nanoparticles and / or polyimide nanofibers.

[0029] More preferably, the polyimide nanoparticles are prepared by ball milling.

[0030] Further preferably, the polyimide nanofibers are prepared by an electrospinning method.

[0031] More preferably, the dispersion liquid is water and / or ethanol.

[0032] More preferably, the auxiliary agent is selected from one or two or more of polyacrylonitrile, polyvinyl alcohol, polyethylene oxide, acrylic acid water-soluble glue, styrene-butadiene rubber, sodium carboxymethyl cellulose, PVDF and polyvinyl pyrrolidone.

[0033] More preferably, the base film is PP and / or PE.

[0034] More preferably, the mixing conditions include: a rotation speed of 500-50000 rpm and a time of 1-5 h.

[0035] More preferably, the drying conditions include: a temperature of 30-100° C. and a time of 1-5 h.

[0036] In the above technical scheme, the polyimide of the present invention has good thermal properties and is resistant to high-temperature decomposition temperatures above 500°C. Due to the presence of strongly polar ether bonds, it has strong adhesion. When it is used to prepare lithium-ion battery separators, the strong adhesion of the polyimide increases the adhesion between the separator and the pole piece. The polyimide tightly connects the ceramic particles and the base film together through its own adhesion, thereby avoiding pulverization and separation of the coating during high-temperature operation of the lithium-ion battery. The polyimide of the present invention has strong affinity with the electrolyte due to the presence of strongly polar ether bonds, thereby improving the wettability of the lithium-ion battery.

[0037] At the same time, the preparation method of the polyimide of the present invention has simple conditions and easy steps. In the process of applying the polyimide to the preparation of the diaphragm in the form of nanofibers and nanoparticles, water is used as the solvent. Compared with the traditional oily organic solvent coating system, the polyimide is green, environmentally friendly, pollution-free, and has lower cost, is suitable for mass production, and is conducive to commercial promotion and use.

[0038] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0040] Figure 1 is a SEM image of the polyimide nanofiber of the present invention;

[0041] Figure 2 is a morphology diagram of a diaphragm prepared using the polyimide of the present invention;

[0042] Figure 3 This is a particle size distribution diagram of the polyimide nanoparticles of the present invention. DETAILED DESCRIPTION

[0043] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0044] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0045] In a first aspect, the present invention provides a method for preparing a polyimide, the preparation method comprising:

[0046] In an inert gas atmosphere, the first solvent, the first monomer and the second monomer are mixed and reacted, pyridine and acetic anhydride are added, refluxed and cooled to obtain a polyimide slurry, the second solvent is added, stirred, filtered and dried.

[0047] The preparation method of the polyimide of the invention has simple conditions and easy-to-operate steps, is suitable for mass production, and is conducive to commercial promotion and use.

[0048] In a preferred embodiment of the present invention, the first solvent is selected from one or two or more of N-methylpyrrolidone, dimethylacetamide and N,N-dimethylformamide.

[0049] In a preferred embodiment of the present invention, the first monomer is selected from one or two or more of aromatic dibasic acid anhydrides, aromatic heterocyclic dibasic acid anhydrides and aliphatic dibasic acid anhydrides.

[0050] In a preferred embodiment of the present invention, the second monomer is a diamine containing an alkyl ether group or a blended diamine obtained by mixing a diamine containing an alkyl ether group with other diamines; wherein,

[0051] The general structural formula of the diamine containing an alkyl ether group is shown in Formula II:

[0052]

[0053] In a preferred embodiment of the present invention, the inert gas is nitrogen and / or argon.

[0054] In a preferred embodiment of the present invention, the second solvent is an alcohol, preferably ethanol and / or methanol.

[0055] In a preferred embodiment of the present invention, the first monomer is selected from one or two or more of biphenyltetracarboxylic dianhydride, cyclobutanetetracarboxylic dianhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, pyromellitic dianhydride, 1,2,3,4-butanetetracarboxylic dianhydride, benzophenonetetracarboxylic dianhydride, 4-phthalic anhydride)formyloxy-4-phthalate, diphenyl ether tetracarboxylic dianhydride, p-phenylene-diphenyltrimethylol dianhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, hexafluoro dianhydride and bisphenol A diether dianhydride.

[0056] In a preferred embodiment of the present invention, the structural formula of the diamine containing an alkyl ether group in the second monomer is selected from one of Formula A to Formula C;

[0057]

[0058] In a preferred embodiment of the present invention, the other diamines in the second monomer are selected from one or two or more of 4,4-diaminodiphenyl sulfone, 3,4-diaminodiphenyl sulfone, 3,3-diaminodiphenyl sulfone, m-phenylenediamine, p-phenylenediamine, pyridinediamine, naphthalenediamine, butanediamine and pentamethylenediamine 3,6-thioanthracene diamine.

[0059] In a preferred embodiment of the present invention, the mass ratio of the first solvent to the first monomer is 3-15:1.

[0060] In a preferred embodiment of the present invention, the molar ratio of the first monomer to the second monomer is 1:0.9-1.2.

[0061] In a preferred embodiment of the present invention, the conditions of the mixed reaction include: temperature of 0-15° C. and time of 1-3 h.

[0062] In a preferred embodiment of the present invention, the reflux reaction time is 4-6 hours.

[0063] In a second aspect, the present invention provides a polyimide prepared according to the preparation method described in the first aspect, wherein the repeating unit of the polyimide comprises: a structure shown in Formula I:

[0064]

[0065] In formula I, X is a group linking two carbonyl groups on the imide ring, which is provided by the first monomer;

[0066] n, a are integers, a, n ≥ 1.

[0067] The polyimide of the present invention has good thermal properties and is resistant to high-temperature decomposition temperatures above 500°C. Due to the presence of strongly polar ether bonds, the polyimide has strong adhesion. When the polyimide is used to prepare a lithium-ion battery separator, the strong adhesion of the polyimide increases the adhesion between the separator and the pole piece. The polyimide tightly connects the ceramic particles and the base film together through its own adhesion, thereby preventing the coating from pulverizing and separating during the high-temperature operation of the lithium-ion battery. Due to the presence of strongly polar ether bonds, the polyimide of the present invention has strong affinity with the electrolyte, thereby improving the wettability of the lithium-ion battery.

[0068] In a third aspect, the present invention provides a use of the polyimide described in the first aspect or the polyimide described in the third aspect in preparing a lithium battery.

[0069] In a fourth aspect, the present invention provides a method for preparing a lithium battery separator, the method comprising: mixing polyimide, ceramic and an additive in the presence of a dispersion to obtain a coating slurry, coating the coating slurry on a surface of a polyolefin base film, and drying; wherein:

[0070] The polyimide is the polyimide described in the second aspect.

[0071] In a preferred embodiment of the present invention, the polyimide is provided in the form of polyimide nanoparticles and / or polyimide nanofibers.

[0072] In a preferred embodiment of the present invention, the polyimide nanoparticles are prepared by ball milling.

[0073] In a preferred embodiment of the present invention, the polyimide nanofibers are prepared by an electrospinning method.

[0074] In a preferred embodiment of the present invention, the method for preparing the polyimide nanofiber comprises: using the polyimide described in the second aspect with electrostatic spinning technology and adjusting the spinning parameters to prepare the polyimide nanofiber material.

[0075] In a preferred embodiment of the present invention, the spinning parameters include: a spinning voltage of 5-60 kV, and a spray distance of 5-40 cm.

[0076] In a preferred embodiment of the present invention, the dispersion liquid is water and / or ethanol.

[0077] In a preferred embodiment of the present invention, the auxiliary agent is selected from one or two or more of polyacrylonitrile, polyvinyl alcohol, polyethylene oxide, acrylic acid water-soluble glue, styrene-butadiene rubber, sodium carboxymethyl cellulose, PVDF and polyvinyl pyrrolidone.

[0078] In a preferred embodiment of the present invention, the base film is PP and / or PE.

[0079] In a preferred embodiment of the present invention, the mixing conditions include: a rotation speed of 500-50000 rpm and a time of 1-5 hours.

[0080] In a preferred embodiment of the present invention, the drying conditions include: a temperature of 30-100° C. and a time of 1-5 hours.

[0081] In a preferred embodiment of the present invention, the coating can be single-sided coating or double-sided coating.

[0082] In a preferred embodiment of the present invention, when preparing a lithium battery separator, the polyimide is provided in the form of polyimide nanofibers, and the polyimide nanofibers are mixed with ceramic coatings. The polyimide nanofiber layer will form a stable network structure on the surface of the base film, thereby enhancing the overall stability of the coating.

[0083] The present invention will be described in detail below through examples. In the following examples, the drugs and pharmaceutical agents are all conventional commercial products.

[0084] Example 1

[0085] Under nitrogen protection, 2 kg N-methylpyrrolidone (NMP) and 218 g pyromellitic anhydride were added to the reactor, the temperature was controlled at 0-15 ° C, 289 g compound A was added, stirred for reaction for 2 hours, 7.9 g pyridine and 10 g acetic anhydride were added, the temperature was raised to 193 ° C and refluxed for reaction for 5 hours, cooled to 25 ° C, 3 kg ethanol was added, stirred for 2 hours, filtered, and the filter cake was dried at 60 ° C for 5 hours to obtain a polyimide product, recorded as B1.

[0086] Example 2

[0087] The method of Example 1 was followed, except that compound A was replaced with an equal amount of compound B to obtain a polyimide product, which was recorded as B2.

[0088] Example 3

[0089] The method of Example 1 was followed, except that compound A was replaced with an equal amount of compound C to obtain a polyimide product, which was recorded as B3.

[0090] Example 4

[0091] The method of Example 1 was followed, except that compound A was replaced with equal amounts of compound A and m-phenylenediamine to obtain a polyimide product, which was recorded as B4.

[0092] Example 5

[0093] The method of Example 1 was followed, except that compound A was replaced with equal amounts of compound A and p-phenylenediamine to obtain a polyimide product, which was recorded as B5.

[0094] Example 6

[0095] The method of Example 1 was followed, except that pyromellitic anhydride was replaced with an equal amount of benzophenone tetracarboxylic dianhydride to obtain a polyimide product, which was recorded as B6.

[0096] Example 7

[0097] The method of Example 1 was followed, except that pyromellitic anhydride was replaced with an equal amount of hexafluorodianhydride to obtain a polyimide product, which was recorded as B7.

[0098] Example 8

[0099] The method of Example 1 was followed, except that pyromellitic anhydride was replaced by an equal amount of hexafluorodianhydride, and compound A was replaced by an equal amount of compound A and 4,4-diaminodiphenyl ether to obtain a polyimide product, which was recorded as B8.

[0100] Comparative Example 1

[0101] The method of Example 1 was followed, except that compound A was replaced with an equal amount of m-phenylenediamine to obtain a polyimide product, which was recorded as D1.

[0102] Application Example 1

[0103] (1) The polyimide B1 prepared in Example 1 was dissolved in NMP to obtain a solution with a solid content of 13%, and electrospun in an electric field with a field strength of 1.2 kV / cm to prepare polyimide nanofibers;

[0104] (2) The polyimide nanofibers, water, ceramics, and additives in step (1) are mixed in a weight ratio of 20:55:20:5, and stirred using a high-speed homogenizer at a speed of 2000 r / min for 1 h to obtain a slurry;

[0105] (3) The slurry is evenly coated on both sides of the PE base film, the base film thickness is 7 μm, and the single-side coating thickness is 2 μm. The coated diaphragm is placed in a drying oven for drying at a drying temperature of 60° C. to obtain a diaphragm;

[0106] The SEM image of the polyimide nanofibers in step (1) is as follows: Figure 1 As shown;

[0107] The morphology of the membrane obtained in step (3) is as follows: Figure 2 shown.

[0108] Depend on Figure 1 It can be seen that the polyimide nanofibers prepared in the present invention have uniform morphology.

[0109] Depend on Figure 2 It can be seen that the diaphragm prepared using the polyimide nanofibers prepared by the present invention has uniform appearance and good coverage.

[0110] Application Example 2

[0111] (1) preparing polyimide nanoparticles by ball milling the polyimide B5 obtained in Example 5, so that the particle size of the polyimide nanoparticles is concentrated in the range of 40-60 nm;

[0112] (2) The polyimide nanoparticles, water, ceramics, and additives in step (1) are mixed in a weight ratio of 20:55:20:5, and stirred using a high-speed homogenizer at a speed of 2000 r / min for 1 h to obtain a slurry;

[0113] (3) The slurry is evenly coated on both sides of the PE base film, the base film thickness is 7 μm, and the single-side coating thickness is 2 μm. The coated diaphragm is placed in a drying oven for drying at a drying temperature of 60° C. to obtain a diaphragm;

[0114] The particle size distribution of the polyimide nanoparticles in step (1) is shown in Figure 3 .

[0115] Depend on Figure 3 It can be seen that the polyimide particles prepared in the present invention have consistent particle sizes and high uniformity.

[0116] Application Example 3

[0117] The method of Application Example 1 was followed, except that the polyimide B2 prepared in Example 2 was used instead of the polyimide B1 prepared in Example 1 to prepare a diaphragm.

[0118] Application Example 4

[0119] The method of Application Example 1 was followed, except that the polyimide B3 prepared in Example 3 was used instead of the polyimide B1 prepared in Example 1 to prepare a diaphragm.

[0120] Application Example 5

[0121] The method of Application Example 1 was followed, except that the polyimide B4 prepared in Example 4 was used instead of the polyimide B1 prepared in Example 1 to prepare a diaphragm.

[0122] Application Example 6

[0123] The method of Application Example 1 was followed, except that the polyimide B5 prepared in Example 5 was used instead of the polyimide B1 prepared in Example 1 to prepare a diaphragm.

[0124] Application Example 7

[0125] The method of Application Example 1 was followed, except that the polyimide B6 prepared in Example 6 was used instead of the polyimide B1 prepared in Example 1 to prepare a diaphragm.

[0126] Application Example 8

[0127] The method of Application Example 1 was followed, except that the polyimide B7 prepared in Example 7 was used instead of the polyimide B1 prepared in Example 1 to prepare a diaphragm.

[0128] Application Example 9

[0129] The method of Application Example 1 was followed, except that the polyimide B8 prepared in Example 8 was used instead of the polyimide B1 prepared in Example 1 to prepare a diaphragm.

[0130] Application Example 10

[0131] The method of Application Example 1 was followed, except that the polyimide D1 prepared in Comparative Example 1 was used instead of the polyimide B1 prepared in Example 1 to prepare a diaphragm.

[0132] Test Example 1

[0133] The diaphragms prepared in Examples 1-10 were tested for heat shrinkage, peel strength and contact angle. The specific test results are shown in Table 1:

[0134] Table 1

[0135]

[0136] It can be seen from the data in Table 1 that the diaphragm product prepared by the present invention has low thermal shrinkage, good heat resistance, high peel strength, and good wettability, which helps to improve the lithium ion transmission efficiency. The diaphragm product prepared by the present invention helps to improve battery safety.

[0137] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0138] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0139] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a polyimide, characterized in that: The preparation method comprises: In an inert gas atmosphere, the first solvent, the first monomer and the second monomer are mixed and reacted, pyridine and acetic anhydride are added, refluxed and cooled to obtain a polyimide slurry, the second solvent is added, stirred, filtered and dried.

2. The preparation method according to claim 1, characterized in that: The first solvent is selected from one or two or more of N-methylpyrrolidone, dimethylacetamide and N,N-dimethylformamide; Preferably, the first monomer is selected from one or two or more of aromatic dibasic acid anhydrides, aromatic heterocyclic dibasic acid anhydrides and aliphatic dibasic acid anhydrides; More preferably, the second monomer is a diamine containing an alkyl ether group or a blended diamine obtained by mixing a diamine containing an alkyl ether group with other diamines; wherein, The general structural formula of the diamine containing an alkyl ether group is shown in Formula II: Further preferably, the inert gas is nitrogen and / or argon; More preferably, the second solvent is an alcohol, preferably ethanol and / or methanol.

3. The preparation method according to claim 1 or 2, characterized in that: The first monomer is selected from one or two or more of biphenyltetracarboxylic dianhydride, cyclobutanetetracarboxylic dianhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, pyromellitic dianhydride, 1,2,3,4-butanetetracarboxylic dianhydride, benzophenonetetracarboxylic dianhydride, 4-phthalic anhydride)formyloxy-4-phthalate, diphenyl ether tetracarboxylic dianhydride, p-phenylene-diphenyltrimethylol dianhydride, 1,4,5,8-naphthalenetetracarboxylic anhydride, hexafluoro dianhydride and bisphenol A diether dianhydride.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The structural formula of the diamine containing an alkyl ether group in the second monomer is selected from one of Formula A to Formula C; 5. The preparation method according to any one of claims 1 to 4, characterized in that: The other diamines in the second monomer are selected from one or two or more of 4,4-diaminodiphenyl sulfone, 3,4-diaminodiphenyl sulfone, 3,3-diaminodiphenyl sulfone, m-phenylenediamine, p-phenylenediamine, 2,2'-bis(trifluoromethyl)-(1,1'-diphenyl)-4,4'-diamine, 4,4-diaminodiphenyl ether, pyridinediamine, 2,5-thiophenedimethylamine, naphthalenediamine, 2,6-pyrimidinediamine, butanediamine and pentamethylenediamine-3,6-thioanthracenediamine.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The mass ratio of the first solvent to the first monomer is 3-15:1; Preferably, the molar ratio of the first monomer to the second monomer is 1:0.9-1.

2.

7. The preparation method according to any one of claims 1 to 6, wherein the conditions of the mixed reaction include: The temperature is 0-15℃ and the time is 1-3h; Preferably, the reflux reaction time is 4-6 hours.

8. A polyimide prepared according to the preparation method according to any one of claims 1 to 7, wherein the repeating unit of the polyimide comprises: The structure shown in formula I: In formula I, X is a group linking two carbonyl groups on the imide ring, which is provided by the first monomer; n, a are integers, a, n ≥ 1.

9. Use of the polyimide according to claim 8 in preparing a lithium battery.

10. A method for preparing a lithium battery separator, characterized in that: The preparation method comprises: In the presence of a dispersion, polyimide, ceramics and an additive are mixed to obtain a coating slurry, and the coating slurry is coated on the surface of a polyolefin base film and dried; wherein, The polyimide is the polyimide according to claim 8; Preferably, the polyimide is provided in the form of polyimide nanoparticles and / or polyimide nanofibers; More preferably, the polyimide nanoparticles are prepared by ball milling; Further preferably, the polyimide nanofibers are prepared by an electrospinning method; More preferably, the dispersion liquid is water and / or ethanol; More preferably, the auxiliary agent is selected from one or two or more of polyacrylonitrile, polyvinyl alcohol, polyethylene oxide, acrylic acid water-soluble glue, styrene-butadiene rubber, sodium carboxymethyl cellulose, PVDF and polyvinyl pyrrolidone; More preferably, the base film is PP and / or PE; More preferably, the mixing conditions include: a rotation speed of 500-50000 rpm and a time of 1-5 h; More preferably, the drying conditions include: a temperature of 30-100° C. and a time of 1-5 hours.

Citation Information

Patent Citations

  • Polyimide coating modified polyolefin composite diaphragm and preparation method thereof

    CN113969006A

  • Novel polyimide microsphere slurry and coated diaphragm thereof

    CN114883746A

  • Insulation paste, positive plate and secondary battery

    CN118755440A

Cited By

  • Battery diaphragm as well as preparation method and application thereof

    CN120565995A